As Representações Sociais de Mulheres em Cargos de Liderança Sobre suas Carreiras em Cooperativas Agroindustriais - Siqueira, Kelen Cristina de Lara (2018)
This dissertation approaches the theme: social representations of women in leadership positions on their careers, in the line of research in Strategy of the Postgraduate Program in Administration (PPGADM), Professional Master in Administration of UNICENTRO. Considering that, despite the evident changes in relation to the role of women, and the consequent ascension in the career they have been achieving, still prevails a disparity in relation to issues of valuation and wage equality of women in relation to men; and that same woman who plays a leading role in an organization, did not leave aside the chores and care of children. In the light of the Theory of Social Representations (MOSCOVICI, 1978), it was sought, as general objective: to understand the social representations that are constructed by women in leadership positions in agribusiness cooperatives on their careers. Thus, the study is a descriptive research with a qualitative approach. For data collection, interviews were conducted with six women in positions of leadership in three agribusiness cooperatives, located in the state of Paraná. Using the technique of content analysis, data were analyzed and interpreted from three categories of analysis: a) the profile of women in positions of leadership; b) personal, social and organizational mechanisms of rise in career, based on studies of O‟NEIL; BILIMORIA, (2005); LOMBARDI, (2006); BOTELHO; MORAES;CUNHA (2008) and SANTOS (2012); c) the participation of women in positions of leadership in the formulation of strategies, considering the approach of strategy as a practice of WHITTIGTON (1996, 2002, 2024, 2006) and JARZABKOWSKI (2007). The results showed that, despite the evident changes in relation to the role of women, and the consequent rise in the career that it has been achieving, there is still male hegemony in organizations, and that this is a consequence, mainly from the stereotypes that appeared in the three mechanisms of ascension in career (personal, organizational and social). Regarding the participation of women in the formulation of strategies, for those surveyed the level of participation is indifferent to gender, but it is related to the positions that they occupy and the areas in which they operate. Thus, there was a contribution to the reduction of the theoretical gap about the theme that involves gender, related to the career of women in positions of leadership, and these, in the approach to strategy as a social practice, located as participants in the formulation of the strategy of organizations, under the perspective of TRS. As a practical contribution to the organizations, the study allows women to better understand, from the voice of women themselves, how the paradigmatic changes of gender relations in organizations have been set up, mainly in what refers to women in leadership positions, so that they can adapt their organizational strategies.